Dialog Antaragama Dan Kontribusi Tokoh Agama Dalam Penyelesaian Konflik Dan Implementasinya Untuk Memperkuat Toleransi - Titin Wulandari Malau (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
In a peaceful society, it is a common need that cannot be avoided amidst differences. The process of dialogue between religious communities becomes important when we talk about the relationship between each religion and belief. Because without dialogue, the ideals of peace and harmony become just empty shadows. This is also due to the existence of dialogue model activities, which is one form of realizing peaceful life in a multicultural society. These results also prove that the existence of an inter-religious dialogue model in conflict resolution is a means of strengthening tolerance between religious groups carried out by society. also as a model for dialogue in community life that meets each other and carries out dialogue on social issues. Apart from that, dialogue on religious experiences, which involves all elements of society, themselves carry out faith traditions, namely prayer based on the guidance of their respective faiths in joint prayer activities at the village hall every year. Religious experience activities are carried out represented by each religious figure. to lead the prayers which are performed alternately. Therefore, the dialogue model between religious communities can be concluded that the life dialogue model of conflict resolution that strengthens tolerance in a pluralistic society can build religious experience and action dialogue that develops in particular communities and this is a very effective solution in building a peaceful community life in particular. in order to create harmony among different people in the midst of our pluralistic society.